Tumor Microenvironment‐"AND" Near‐Infrared Light‐Activated Coordination Polymer Nanoprodrug for On‐Demand CO‐Sensitized Synergistic Cancer Therapy. Issue 7 (11th December 2020) - Sun, Panpan; Jia, Le; Hai, Jun; Lu, Siyu; Chen, Fengjuan; Liang, Kun; Sun, Shihao; Liu, Hanwen; Fu, Xu; Zhu, Yanhong; Wang, Baodui
Abstract: Carbon monoxide (CO) as an emerging treatment holds great promise for inducing the apoptosis of cancer cells. Here coordination assembled strategy is first reported for synthesis of Cu(II)‐flavone coordination polymer (NCu‐FleCP) CO nanoprodrug that is stable in normal physiological conditions, and yet readily reduces to small size prodrug complex and releases CO on demand under glutathione (GSH) and near infrared (NIR) light. Specifically, after uptaking by cancer cells, local GSH attacked coordination bond within NCu‐FleCP, resulting in the release of Cu(I) and free Fle. The CC bond of Fle is cleavage under NIR light to release CO for gas therapy, and Cu(I) reacts with local H2 O2 through Fenton like reaction to generate hydroxyl radicals ( OH) for chemodynamic therapy. Detailed in vitro and in vivo experiments demonstrate that the CO prodrug system in generating a sufficient quantity of CO and OH offers remarkable destructive effects against cancer cells without causing toxicity to surrounding normal tissues. The study provides a solid foundation to develop smart coordination polymer CO prodrugs with on‐demand CO release, enhanced permeability and retention effect, and biodegradability for multimodal synergistic therapy. Abstract : A microenvironment‐ "AND" near infrared (NIR) light‐sequentially responsive dual responsive Cu(II)‐flavone coordination polymer nanoreactor is reported, which possesses the in situ generation of hydroxyl radicals (OH) and carbon monoxide (CO) based on the specific sequential reactions at the tumor sites for tumor‐specific CO and chemodynamic synergistic therapy.